Impact of different waves of COVID-19 on the rate and indications of Caesarean delivery: An Observational Study - Meena, Deepika; Puri, Manju; Jaiswal, Nishtha; Kumar, Manisha; Handa, Anu; Nain, Shilpi (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To assess the impact of the COVID-19 pandemic on caesarean section rate, its indications, and related maternal and neonatal mortality rates during the first and second waves in comparison to pre-COVID era. Methods: This is retrospective observational analytical study conducted at a tertiary hospital from Northern India. Case records of 3196 women who underwent caesarean delivery (CD) during pre-Covid, Covid first wave and covid second wave periods from April to September each year in 2019, 2020 and 2021 respectively were reviewed. Results: Institutional delivery rate reduced by 45% and 38% during first and second waves respectively. The overall CD rate in the study groups 1 (29.34%) and 2 (30.09%) was comparable with control group (28.70%). Difference in CD rate in COVID-19 positive and negative women was comparable. The most common indication for CD was foetal distress followed by labour dystocia in all groups. Caesarean delivery for failed induction was significantly reduced in both waves. However, CD for previous two or more caesarean sections and non-reassuring FHR were significantly increased in first wave and for deranged doppler in second wave. Maternal mortality ratio and neonatal mortality rate were comparable in all groups. Conclusions: Institutional delivery rate significantly reduced in COVID-19 pandemic with non-significant change in caesarean section rate and significant difference in few indications Keywords: cesarean delivery, cesarean section, COVID-19, maternal mortality, neonatal mortality